THE RESISTANCE OF MARGINALIZED PEOPLE IN “KEN AROK DAN KEN DEDES” NOVEL BY GAMAL KOMANDOKO - Haris Supratno; Darni Darni; Tengsoe Tjahjono; Nashruddin Nashruddin (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
Literary works has been used as objects of research as well as instruments for studying theories of language and literature. One of the literary works that is involved in linguistics and literature research is novel. This study aims at (i) finding the influence of dominant and arbitrary authorities, (ii) finding the resistance of the marginalized people against the authorities, and (iii) revealing the intelligence of the marginalized in doing an effort to fight against the authorities, in a novel entitled “Ken Arok dan Ken Dedes (Pertumpahan Darah Menuju Singgasana)” composed by Gamal Komandoko by applying Gayatri Spivak’s post-colonial theory. The present study uses a qualitative approach in which the data source is a novel of “Ken Arok dan Ken Dedes (Pertumpahan Darah Menuju Singgasana)” telling a coup story in Java. The research data are words, phrases, sentences, and paragraphs, found in Komandoko’s novel, which are in line with Spivak’s post-colonial theory. The researchers used documentation or literature in data collection. For data analysis, the researchers used descriptive analysis technique. From the results of data analysis based on Spivak’s post-colonial theory, the influence of authorities which are dominant and arbitrary, the resistance of the marginalized people against the authorities, and high intelligence possessed by the marginalized to carry out a coup as a form of resistance against the authorities are found in the novel of “Ken Arok dan Ken Dedes (Pertumpahan Darah Menuju Singgasana)” by Gamal Komandoko.